2016
DOI: 10.1161/atvbaha.116.306874
|View full text |Cite
|
Sign up to set email alerts
|

Do the Apoe −/− and Ldlr −/– Mice Yield the Same Insight on Atherogenesis?

Abstract: Murine models of atherosclerosis are useful for investigating the environmental and genetic influences on lesion formation and composition. Apoe−/− and Ldlr−/− are the two models most extensively used models. The models differ in important ways with respect to the precise mechanism by which their absence enhances atherosclerosis, including differences in plasma lipoproteins. The majority of the gene function studies have utilized only one model, with the results being generalized to atherogenic mechanisms. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(84 citation statements)
references
References 86 publications
5
79
0
Order By: Relevance
“…Furthermore, in their study no effect was observed on cholesterol metabolism, whereas we detected a reduction in LDL cholesterol levels. Considering that the above experiments were performed in apoE −/− mice, it is possible that strain specific effects are responsible for the different mechanism observed40. In the past, numerous studies have examined the differences between the LDLr −/− and apoE −/− models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in their study no effect was observed on cholesterol metabolism, whereas we detected a reduction in LDL cholesterol levels. Considering that the above experiments were performed in apoE −/− mice, it is possible that strain specific effects are responsible for the different mechanism observed40. In the past, numerous studies have examined the differences between the LDLr −/− and apoE −/− models.…”
Section: Discussionmentioning
confidence: 99%
“…34 One of the most commonly used mouse models of atherosclerosis is apoE −/− mice. 35 apoE −/− mice spontaneously develop hypercholesterolemia because of increased chylomicron remnant, very low-density lipoprotein (VLDL) and LDL cholesterol, with total cholesterol concentrations ranging from 300 to 500 mg/dL. 36,37 Although the rate of atherosclerotic lesion development varies greatly between facilities, macrophage foam cells can be present in the aortic root within a month.…”
Section: Micementioning
confidence: 99%
“…The comparison of mouse models of atherosclerosis is beyond the scope of this review and has been summarized elsewhere. 104, 105 …”
Section: Co-stimulatory Pathways In Atherosclerosismentioning
confidence: 99%